Isidoro J. Ruiz Moreno, Literatura Histórica. Martín Ruiz Moreno y la Organización Nacional, Buenos Aires, Librería Histórica, 2006, 243 pp. - Carsen, María Victoria (2007)
Fil: Carsen, María Victoria. Pontificia Universidad Católica Argentina; Argentina